Corporate social responsibility and Library collaborative partnership - Khoir, Safirotu (Persatuan Pustakawan Malaysia, 2011)
Corporate social responsibility (CSR) for libraries has been done by companies in Indonesia in the last few years. In an academic library, this partnership creates mutually beneficial collaboration for both company and library. Gadjah Mada University Library has established several partnerships with companies and other parties. The form of partnership is divided into two categories: building small and special spaces within an academic library and financially supporting library activities. Several partnerships have resulted in the establishment of the American Corner, Hatta Corner, World Bank Corner, Sampoerna Corner and Nation Building Corner (NBC). The latest is the newest partnership. This article discusses the collaboration between library and other parties to support the library users based on direct observation and in-depth interviews. NBC is the “youngest” corner in the Library. It was established collaboratively with the University, National Power Plant and Nurani Dunia Foundation in 2009. NBC has already supported the services of the Library with several facilities and activities for the users such as conducting events for users such as book reviews and discussions on recent national issues. The book review invites the author and another speaker to criticize the book from different perspectives. In its first year, NBC built partnership with Kampung Halaman Foundation and Ford Foundation which provides amateur community video about the Indonesian culture, economics, social life, ideology and others. Recorded by the local community and amateurs, these video can be accessed via special databases and are free to download and share for community development. The existence of CSR has contributed to the library services for users. The company benefits from CSR because the library users can identify company’s profile and its products. This mutual partnership supports both parties provisionin of excellent services.